1988
DOI: 10.1007/bf00017467
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a negatively light-regulated mRNA from Lemna gibba

Abstract: We have isolated a cDNA clone, called pLg106, which corresponds to a negatively light-regulated mRNA in the aquatic monocot Lemna gibba. Lg106 mRNA is more abundant in dark-treated plants than in plants grown under continuous white light. The levels of Lg106 mRNA reached a maximum 12-24 hours after plants had been placed in the dark. In vitro-labelled transcripts from nuclei isolated from white light-grown and darktreated Lemna hybridized equally to Lg106 DNA, indicating that transcription of the Lg106 gene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1990
1990
1991
1991

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The dark-induced accumulation of the ASI mRNA classifies the AS 1 gene with other genes that are negatively regulated by light such as phytochrome (Otto et al, 1984;Lissemore and Quail, 1988;Kay et al, 1989), protochlorophyllide reductase (Mosinger et al, 1985) and an unidentified mRNA found in Lemna (Okubara et al, 1988). As shown for phytochrome (Lissemore and Quail, 1988;Kay et al, 1989) and protochlorophyllide reductase genes (Mosinger et al, 1985), the repression of ASI mRNA accumulation in the light is a phytochrome-mediated response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The dark-induced accumulation of the ASI mRNA classifies the AS 1 gene with other genes that are negatively regulated by light such as phytochrome (Otto et al, 1984;Lissemore and Quail, 1988;Kay et al, 1989), protochlorophyllide reductase (Mosinger et al, 1985) and an unidentified mRNA found in Lemna (Okubara et al, 1988). As shown for phytochrome (Lissemore and Quail, 1988;Kay et al, 1989) and protochlorophyllide reductase genes (Mosinger et al, 1985), the repression of ASI mRNA accumulation in the light is a phytochrome-mediated response.…”
Section: Discussionmentioning
confidence: 96%
“…As shown for phytochrome (Lissemore and Quail, 1988;Kay et al, 1989) and protochlorophyllide reductase genes (Mosinger et al, 1985), the repression of ASI mRNA accumulation in the light is a phytochrome-mediated response. However, it remains to be determined whether the dark-induced (or light-repressed) expression of ASI reflects a transcriptional response as has been shown for phytochrome (Lissemore and Quail, 1988;Kay et al, 1989) and protochlorophyllide reductase (Mosinger et al, 1985) or whether it represents a post-transcriptional response as has been shown for another dark-induced gene of unknown function (Okubara et al, 1988). In direct contrast to the dark-induced accumulation of AS1 mRNA in leaves, the mRNA for the chloroplast form of glutamine synthetase (GS2) accumulates in the light in a phytochrome-mediated response (Tingey et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of j3-tubulin mRNA abundance has also been observed after transfer of etiolated soybean seedlings to white light (1). The mRNA levels of at least 11 genes encoding unknown proteins (8,20) exposure of dark grown plants to white light. The mRNA abundance of at least one of these genes is unaffected by red light, indicating that this gene is not under phytochrome control (20).…”
Section: Discussionmentioning
confidence: 95%
“…The mRNA levels of at least 11 genes encoding unknown proteins (8,20) exposure of dark grown plants to white light. The mRNA abundance of at least one of these genes is unaffected by red light, indicating that this gene is not under phytochrome control (20). The down-regulation of the phytochrome, asparagine syntetase, and protochlorophyllide reductase mRNAs is phytochrome-mediated (4,5,19,29).…”
Section: Discussionmentioning
confidence: 99%